Raspberry Pi cookbook for Python programmers : over 50 easy-to-comprehend tailor-made recipes to get the most out of the Raspberry Pi and unleash its huge potential using Python /: over 50 easy-to-comprehend tailor-made recipes to get the most out of the Raspberry Pi and unleash its huge potential using Python. (2014) - Unknown
No abstract available